The Application of Stem Cells in the Field of Cosmetic Medicine The Aspect of Islamic Law - Rizka Rizka; Septarina Budiwati (Journal of Social Science, 2022)
The discovery of stem cells, which are not only utilized in many medical treatments but are also recognized to be beneficial to aesthetic treatments, served as the impetus for this research. It is necessary for anybody who wants to stay beautiful and healthy, free from illness caused by diminished organ performance or damage, that it has the ability to replace dead cells with new cells that are youthful and healthy. The usage of stem cells in the treatment of anti-aging by so many women Because the origin of Stem Ceis remained in the pros and cons, the objective of this study is to find out the legislation on the usage of Stem Cells from an Islamic point of view. This is because the pros and cons of the source of Stem Ceis are still being debated. study employs the library method by ll retrieval to acquire data about stem cells and their uses for beauty and Islamic law from a variety of sources including books and journals. Method is used to collect information. The findings demonstrated that, from the viewpoint of Islamic law, the utilization of stem cells for the purposes of esthetic beauty and anti-aging is forbidden for any reason whatsoever due to the fact that they are exclusively for non-urgent requirements. The utilization of stem cells is typically done for beneficial purposes; it does not violate norms, ethics, or religion; it does not result in damage; and it respects the creation that was made by the Creator.